Autophagy-related protein PIK3C3/VPS34 controls T cell metabolism and function: PIK3C3/VPS34 in T cell metabolism and function - Yang, Guan (Autophagy, 2020)
The PIK3C3/VPS34 subunit of the class III phosphatidylinositol 3-kinase (PtdIns3K) complex is a key early player in macroautophagy/autophagy. In this study, we assessed the contribution of PIK3C3 to T cell metabolism and function. We found that Pik3c3-deficient T cells exhibited impaired cellular metabolism, and Pik3c3-deficient CD4(+) T cells failed to differentiate into T helper 1 cells. These alterations were associated with reduced levels of active mitochondria upon T cell activation. In addition, conditional Pik3c3-deficient animals failed to mount autoreactive T cell responses and were resistant to experimental autoimmune encephalomyelitis (EAE). Interestingly, the deletion of Pik3c3 had little effect on the capacity of animals to clear tumor metastases. Collectively, our studies have revealed a critical role of PIK3C3 in T cell metabolism and the pathogenicity of these cells during EAE. Our findings also have important implications for the development of immunotherapies to treat multiple sclerosis and other inflammatory diseases by targeting PIK3C3. Abbreviations: CNS: central nervous system; DC: dendritic cell; DEG: differentially expressed gene; EAE: experimental autoimmune encephalomyelitis; ECAR: extracellular acidification rate; iNKT: invariant natural killer T; LAP: LC3-associated phagocytosis; LLC: Lewis lung carcinoma; MAP1LC3/LC3: microtubule-associated protein 1 light chain 3; MDSC: myeloid-derived suppressor cell; MOG: myelin oligodendrocyte glycoprotein; NK: natural killer; OCR: oxygen consumption rate; PI: propidium iodide; PIK3C3/VPS34: phosphatidylinositol 3-kinase catalytic subunit type 3; RNA-seq: RNA-sequencing; TCR: T cell receptor; TMRE: tetramethylrhodamine ethyl ester perchlorate